The Paris climate agreement - Harris, Duchess; Rowell, Rebecca (Special reports (Essential Library (Firm)), 2019)
Examines the Paris Climate Agreement, discussing its goals, positive and negative aspects, and impact on the future. Includes sidebars, a glossary, resources for further information, maps, and color photographs.